Signifying Resistance: A Semiotic Analysis of Patriarchal Culture and Female Agency in Khaled Hosseini's A Thousand Splendid Suns - Andi Niftah; Abd Halim; Muhammad Hasbi (Interling : International Journal of English Language Teaching, Literature and Linguistics, 2026)
Patriarchal culture remains a persistent social issue and is frequently represented in literary works as a system that shapes women’s identities, experiences, and social positions. This study aims to examine how patriarchal culture is represented in Khaled Hosseini’s A Thousand Splendid Suns through Roland Barthes’ semiotic framework. Employing a qualitative textual analysis design, the study uses the novel as its primary data source. The data consist of dialogues, narrative descriptions, and character interactions depicting patriarchal practices, which were collected through close reading, systematic note-taking, and textual categorization. Data were analyzed at three levels of signification denotation, connotation, and myth to uncover both explicit and ideological meanings embedded in the text. The findings reveal that patriarchal culture is constructed through four interconnected domains: household, sexuality, violence, and cultural institutions. At the denotative level, these domains depict women’s exclusion from decision-making, control over female sexuality, domestic abuse, and educational restrictions. At the connotative level, they signify unequal gender relations that privilege male authority and female subordination. At the mythical level, the novel naturalizes cultural beliefs that legitimize male dominance, female obedience, son preference, and the normalization of women’s suffering. The study concludes that A Thousand Splendid Suns represents patriarchy as a socially and ideologically constructed system sustained through interconnected cultural myths. By applying Barthes’ semiotic framework, the study demonstrates how the novel simultaneously exposes and critiques the ideological mechanisms that perpetuate gender inequality.